Solubility and Dissolution Rate Enhancement of Aceclofenac by Solid Dispersion Employing Kneading and Solvent Evaporation Techniques - Alezzy, Ahmad Abdullah Essa (Tikrit Journal of Pharmaceutical Sciences, 2024)
Background: Aceclofenac (ACF) is a non-steroidal anti-inflammatory drug with potent anti-inflammatory and analgesic properties. ACF is belongs to BCS class II which has poor solubility in water (practically insoluble) and high permeability that leads to a low dissolution rate and reduced bioavailability. Objective: to enhance the solubility and dissolution rate of ACF using the solid dispersion method (SD) by two common techniques which were solvent evaporation (SE) and kneading (Kn) by using different carriers Mannitol, PVP k30, Soluplus®, and Urea in both techniques at 1:1 and 1:5 wight ratio. Methods: The effects of type of carrier and preparation method on solubility and dissolution rate of SD were studied. Solid dispersions were characterized for their, percentage yield, drug content, drug solubility and in-vitro dissolution rate in comparison with pure drug. Results: The best formula is obtained by the Kn formula (F16) which was formulated by the use of ACF: Soluplus®: with a weight ratio of 1:5 which gave a high percentage yield (99.5%), high drug content (99.8± 0.003%) and the best solubility enhancement which was 361 folds compared to pure ACF and faster dissolution rate which was 80% in 10 minutes compared to 20% for pure drug. Conclusion: the solubility and in-vitro dissolution rate of ACF was efficiently improved when prepared by SD techniques, utilizing both solvent evaporation and kneading methods. Furthermore, the kneading method was superior to solvent evaporation method due to the greater enhancement of solubility and dissolution rate obtained by all carriers and ratios with higher improvement by 1:5 ratio, and can be considered a successful and efficient strategy for solubility and in-vitro dissolution rate improvement of hydrophobic drugs.